Pendekatan Restorative Justice Dalam Penyelesaian Tindak Pidana Pencemaran Nama Baik Di Bidang Informasi dan Transaksi Elektronik - Viona Juanne Huwae; Deassy Jacomina Anthoneta Hehanussa; Iqbal Taufik (Faculty of Law Universitas Pattimura, 2023)
ABSTRACT: Defamation by means of social media is indeed easy to do and spreads quickly and is known by many people. This has an adverse impact on other people which has legal implications as contained in Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008, Article 36 as referred to in articles 27 to 34 which result in losses for other people. This study uses the Normative Juridical method with the Study of Statutory Approaches, Case Approaches, and Conceptual Approaches. Legal Material Collection Techniques are carried out using library research. The sources of legal material used in this study are the study of primary legal materials, the study of secondary legal materials, and the study of tertiary legal materials. The legal materials are analyzed using a qualitative approach. The results of the study show that the Restorative Justice Approach is used in solving criminal acts of defamation in the field of ITE as an alternative in seeking peace so that prison sentences are no longer imposed, and the process is replaced by mediation involving the perpetrator, victim, perpetrator's family, and/or the victim's family and stakeholders. The application of Restorative Justice must be carried out on specific crimes, especially on defamation crimes which are an alternative in the law enforcement process. The Restorative justice approach to criminal acts of defamation in the field of ITE needs to be carried out to protect a person's dignity from acts of insult and the Government must make a legal basis such as a Law that further regulates Restorative Justice, so that its application is more optimal.